PERILAKU PETANI SAYURAN DALAM MENCARI INFORMASI PERTANIAN MENGGUNAKAN INTERNET - Yusra Muharami Lestari (JURNAL AGROTEKNOSAINS, 2020)
This study aims to determine the level of internet use of vegetable farmers and to analyze what factors influence farmer behavior in searching for agricultural information using the internet in Medan Marelan District, Medan City. The research method used is descriptive quantitative by collecting information through observation, distributing questionnaires and interviews. The data analysis method was carried out by calculating the acquisition score and multiple linear analysis. The results showed that the level of farmer behavior in searching for agricultural information using the internet was high at 76.5%. Based on the test results of multiple linear analysis, the effect of independent variables on farmer behavior is 68.5%, while the remaining 31.5% is influenced by other factors.